Investigation on variation mechanisms of ash fusion and viscosity of high calcium-iron coal by coal blending. (15th February 2023) - Zhao, Wei; Li, Fenghai; Ma, Mingjie; Zhao, Chaoyue; Wang, Yong; Yang, Ziqiang; Zhang, Xujing; Fang, Yitian
Highlights: Ash fusion temperature (AFT) of MO mixture increased from slowly, rapidly, and slowly. Hauyne disappearance and anorthite formation caused AFT increase with P4 addition. The shift of Si-O and Si-O-Al to the high-frequency region caused ash viscosity increase. The increases in R-value and bridging oxygen bond led to mixed ash viscosity increases. Abstract: In this work, the ash fusion temperature (AFT) and viscosity modification behaviors of high calcium-iron coal ash (MO) were investigated by blending coal with high silicon-aluminum coal ash (P4). X-ray powder diffractometer (XRD), Fourier transform infrared spectrometer (FT-IR), Raman, and FactSage thermodynamic software were selected to investigate the AFT and viscosity change mechanisms. With the increase of P4 mass ratio, the AFT of MO mixtures increased from slowly (0–20 %) to rapidly (20 %–30 %), and then to slowly (30 %–50 %), and the ash viscosity also increased correspondingly. When the amount of P4 was in the range of 30–40 %, the flow temperature (FT) and viscosity of ash samples were 1368–1395 °C and 4.28–5.02 Pa·s, respectively, which met the requirements of entrained-flow bed gasification slag tapping. The XRD results showed that the disappearance of hauyne and the formation of anorthite were the main reasons for the mixed MO AFT increase. With the increasing P4 mass ratio, Si-O and Si-O-Al in ash samples moved to the high-frequency region in FT-IR, indicating the formations of more stable silicate network structures; the R-value (R = (Q 3 + Q 2 )/(Q 1 + Q 0 )) gradually increased indicating the increases in polymerization degree. The both led to the increases in viscosity. The decreasing ratio of non-bridged oxygen bond to bridged oxygen bond with increasing P4 percentage also explained the AFT and viscosity variation.